Analisis jejak karbon pada produksi ayam potong dengan pendekatan life cycle assessment - Silmi Azmi; Junervin Junervin; Syamsuwarni Rambe; Muhammad Luqmanul Hakim; Amina Kurniasi Alu (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Broiler chicken agroindustry has significant potential to produce carbon emissions from using resources, energy, and waste. Awareness of environmental sustainability encourages the industry to improve its production system to be more environmentally friendly. Before improving the production system, carbon emission analysis needs to be carried out in the production process to assess its impact. This study aimed to evaluate the impact of global warming throughout the life cycle of broiler chicken products through carbon footprint analysis using the Life Cycle Assessment (LCA) method. The data inventory consisted of inputs and outputs from three subsystems: feed production, broiler chicken production, and chicken meat production. The impact calculation used the CML-IA (Center of Environmental Science of Leiden University) baseline method on the SimaPro software. The results showed that 1 kg of frozen packaged carcass produced a carbon footprint of 4.35 kg CO2 eq. Feed production, especially soybean meal, bio waste, and electricity use, were the primary sources of emissions in the three subsystems. Improvement scenarios to reduce the carbon footprint included substituting soybean meal with local feed ingredients, processing biowaste into compost, and increasing energy efficiency in the cooling system